What Is Veiling? - Amer, Sahar (Book collections on Project MUSE., 2014)
Examines the practice of veiling in Muslim culture, discussing its history, its religious, social, and political significance, and its importance to both conservative and progressive Muslim women as a symbol of commitment to their beliefs.--Publisher's description.